Stealing America : the hidden story of Indigenous slavery in US history - Fisher, Linford D. (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2026)
"Decades in the making, Linford Fisher's Stealing America is the first comprehensive history of indigenous slavery in North America. While there have been regional and state histories of indigenous slave history, Fisher's book examines the practice of European enslavement of native people in its entirety from the late sixteenth century well into the twentieth century. Initially a Ph.D. student under Jill Lepore and now a tenured professor at Brown, Fisher presents a dramatic and sweeping narrative, demonstrating how indigenous enslavement was a massive phenomenon that spanned the entire Americas and ensnared between 2.5 and 5 million Native Americans between 1492 and 1900. After the defeat of the Spanish Armada, an unparalleled frenzy of explorers usurped native land, stealing hundreds of thousands of indigenous people in the process. From New England to Texas to California, colonizers enslaved Native people and disguised the act, treating them as Black slaves, in order to avoid detection since the enslavement of Natives was a source of shame to the English and later made illegal. Native slavery would then be covertly merged with Black slavery, the two populations being counted under one rubric. In fact, this use of Native slavery precedes Black slavery and 1619 by over 40 years, effectively rewriting American history at its origins. As Fisher re-narrates early America, Native slavery makes appearances in ways we had no idea, whether in the post-1804 Louisiana Purchase; at Sutter's Mill, where hundreds if not thousands of native slaves were used to "discover" gold; or in the forced adoptions and in "Indian" schools well into the twentieth century. With Stealing America, Fisher has created a sprawling, potentially prize-winning masterpiece that will certainly establish him as one of our leading American historians"-- Provided by publisher.